2023
DOI: 10.1021/acs.chemmater.2c03612
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione/Glucose-Depleting Nanoparticles with NO Generation for Ferroptosis/Starvation/NO-Induced Cancer Therapy

Abstract: Depleting intracellular glutathione (GSH) has emerged as a potent strategy to combat cancer. However, the existing GSH-depleting agents are too toxic or ineffective and standalone GSH depletion fails to yield a satisfactory curative effect. Herein, we present an intelligent nanoparticle that possesses GSH depletion, glucose consumption accompanied with H2O2 production, and NO generation properties for multimodal cancer therapy. The nanoparticle is constructed by synthesis of tetrasulfide bond-doped mesoporous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…32,33 DTNB has its characteristic absorption band centered at 312 nm and exhibits a red shift to 412 nm upon reaction with GSH, which is due to the formation of 2-nitro-5-thiobenzoic acid. 34 In order to study GSH depletion by the NPs, GSH (25 μM) was incubated with β-CD + /1 NPs (25 μM), H 2 O 2 (100 μM) and DTNB (10 μM) for 0.5 h, and the absorption spectral changes were then monitored. As a control experiment, the absorption spectrum of the reaction mixture containing GSH and DTNB without β-CD + /1 NPs and H 2 O 2 was recorded.…”
Section: Resultsmentioning
confidence: 99%
“…32,33 DTNB has its characteristic absorption band centered at 312 nm and exhibits a red shift to 412 nm upon reaction with GSH, which is due to the formation of 2-nitro-5-thiobenzoic acid. 34 In order to study GSH depletion by the NPs, GSH (25 μM) was incubated with β-CD + /1 NPs (25 μM), H 2 O 2 (100 μM) and DTNB (10 μM) for 0.5 h, and the absorption spectral changes were then monitored. As a control experiment, the absorption spectrum of the reaction mixture containing GSH and DTNB without β-CD + /1 NPs and H 2 O 2 was recorded.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the ROS sensitivity of nanoliposome (LIPSe), 200 μg of LIPSe was added into 1 mM H 2 O 2 with dipotassium titanium oxide dioxalate as an indicator. As well reported, TiO bonds could react with H 2 O 2 to yield yellow color, which had a good linear relationship existing between the maximum absorption of H 2 O 2 /Ti­(IV) and H 2 O 2 concentration. As presented in Figure S5, LIPSe treatment caused significant decrease in H 2 O 2 concentration over time while LIP (nanoliposome without diselenide bonds incorporation) treatment did not reduce H 2 O 2 concentration. This indicated that the incorporated diselenide bonds of the nanoliposome could consume H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…As well reported, TiO bonds could react with H 2 O 2 to yield yellow color, which had a good linear relationship existing between the maximum absorption of H 2 O 2 /Ti­(IV) and the H 2 O 2 concentration. Therefore, in order to confirm the ROS sensitivity of LIPSe, 200 μg of LIPSe was added into 1 mM H 2 O 2 with dipotassium titanium oxide dioxalate as an indicator. After incubation for 1, 2, 4, 6, and 10 h, the absorbance was recorded by UV–vis spectroscopy to calculate the H 2 O 2 depletion and evaluate the ROS sensitivity ability of LIPSe.…”
Section: Methodsmentioning
confidence: 99%
“…While several studies have been devoted to MSNs, [147][148][149] PSiNPs, [150][151][152] MOFs, [153][154][155] COFs, [156][157][158] HOFs [159] and carbon porous materials [160,161] in pre-clinical evaluation for cancer therapy, deeper in vivo studies are essential to understand the biodistribution and biosafety of the current advanced porous materials to reach effective infectious disease treatment and, ultimately, be translated to clinical trials.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%